2007
DOI: 10.1007/s10722-006-9120-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in Turkish melons (Cucumis melo L.) based on phenotypic characters and RAPD markers

Abstract: The genetic relationships among 56 melon (Cucumis melo L.) genotypes collected from various parts of Turkey were determined by comparing their phenotypic and molecular traits with those of 23 local and foreign melon genotypes to investigate the taxonomic relationships and genetic variation of Turkish melon germplasm. Sixty-one phenotypic characters and 109 polymorphic RAPD markers obtained from 33 primers were used to define the genetic similarity among the melon genotypes by dendrograms or two and three dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 42 publications
7
41
0
Order By: Relevance
“…The genetic difference between horticultural groups of melon has been studied by analysis of the isozyme (Kato et al 1998) and by using RAPD (Silberstein et al 1999, Stepansky et al 1999, Feyzian et al 2007, Sensoy et al 2007. However, these studies clustered together Inodorus, Cantalupensis and Flexuosus, and thus none of the studies succeeded in separating the three groups of largeseed type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic difference between horticultural groups of melon has been studied by analysis of the isozyme (Kato et al 1998) and by using RAPD (Silberstein et al 1999, Stepansky et al 1999, Feyzian et al 2007, Sensoy et al 2007. However, these studies clustered together Inodorus, Cantalupensis and Flexuosus, and thus none of the studies succeeded in separating the three groups of largeseed type.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers, such as amplified fragment length polymorphism (AFLP; Garcia-Mas et al 2000, Yashiro et al 2005, random amplified polymorphic DNA (RAPD; Mliki et al 2001, López-Sesé et al 2003, Nakata et al 2005, Dhillon et al 2007, Tanaka et al 2007, Yi et al 2009) and simple sequence repeats (SSRs; Monforte et al 2003, Nakata et al 2005, Dhillon et al 2007, have been intensively used in diversity analysis of melon. Morphological and physiological data were combined with RAPD data to analyze the genetic diversity of melon in Turkey (Sensoy et al 2007), India (Dhillon et al 2007), Myanmar (Yi et al 2009) and China (Luan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…C. melo is, therefore, considered the most diverse species in Cucumis (Stepansky et al 1999). Genetic diversity studies have used isozymes (Staub et al 1997;Akashi et al 2002), RFLPs (Zheng et al 1999), RAPDs (Garcia et al 1998;Stepansky et al 1999;Mliki et al 2001;López-Sesé et al 2003;Staub et al 2004;Sensoy et al 2007;Tanaka et al 2007), AFLPs (GarciaMas et al 2000), ISSR and simple-sequence repeat (SSR) (Katzir et al 1996;Staub et al 2000;Daning-Poleg et al 2001;López-Sesé et al 2002;Monforte et al 2003;Nakata et al 2005;Tzitzikas et al 2009) to analyze variability and relationships among melon groups. These studies have assisted in the elucidation of intraspecific relationships in melons from different origins.…”
Section: Introductionmentioning
confidence: 99%
“…High percentage of polymorphism based on ISSR markers was obtained by Paris et al (2003) in Cucurbita pepo (74%); Behera et al (2008) in Momordica charantia and Verma et al (2007) in Benincasa hispida (>80%). These studies demonstrated that ISSR markers frequently detected a higher level of polymorphism than that detected with other dominant markers (RAPD or AFLP) among Citrullus or other Cucurbitaceae (Paris et al, 2003;Sensoy et al, 2007;Behera et al, 2008). Stepansky et al (1999) showed in Cucumis melo L. the same trend i.e.…”
Section: Discussionmentioning
confidence: 83%